THE RELATIONSHIP OF FARMER SOCIAL ECONOMIC CHARACTERISTICS TO THE SUCCESS OF AGRICULTURAL EXPLANATION PROGRAM LEGOWO 4:1 PLANTING SYSTEM AND SRI (System of Rice Intensification) (Case Study: Pematang Setrak Village, Teluk Mengkudu District, Serdang Bedagai - Muhammad Syahrizal (Institute of Computer Science (IOCS), 2021)
This study aims to determine the socio-economic characteristics of farmers in the research area, determine the success of agricultural extension programs on the Legowo 4:1 planting system and SRI (System Rice of Intenfication) in the research area, determine the success rate of implementing agricultural extension programs on the Legowo 4:1 planting system and SRI (System Rice of Intenfication) in the research area, to find out whether there is a relationship between the socio-economic characteristics of farmers (age, education level, length of farming , number of dependents) on the success of agricultural extension programs on the Legowo 4:1 planting system and SRI (System Rice of Intensification). ) in the study area. The analysis method uses descriptive, scoring, and Rank Spearman methods with the help of SPSS 16. The results obtained that the success rates of the extension program on the Legowo 4:1 planting system and SRI (System Rice of Intenfication) were 81.5% and 83.7% respectively. Age and duration of farming have a relationship with the success of the agricultural extension program in the 4:1 legowo planting system. Meanwhile, the level of education and the number of dependents have no relationship to the success of the agricultural extension program in the 4:1 legowo planting system. While the level of education, length of farming and number of dependents have no relationship to the success of the agricultural extension program on the SRI (System Rice of Intenfication) planting system. Age and duration of farming have a relationship with the success of the agricultural extension program in the 4:1 legowo planting system. Meanwhile, the level of education and the number of dependents have no relationship to the success of the agricultural extension program in the 4:1 legowo planting system. While the level of education, length of farming and number of dependents have no relationship to the success of the agricultural extension program on the SRI (System Rice of Intenfication) planting system. Age and duration of farming have a relationship with the success of the agricultural extension program in the 4:1 legowo planting system. Meanwhile, the level of education and the number of dependents have no relationship to the success of the agricultural extension program in the 4:1 legowo planting system. While the level of education, length of farming and number of dependents have no relationship to the success of the agricultural extension program on the SRI (System Rice of Intenfication) planting system.